Transcriptional Dynamics Underlying Somatic Embryogenesis in Coffea canephora - Marcos-David Couoh-Cauich; Hugo A. Méndez-Hernández; Rosa M. Galaz-Ávalos; Ana Odetth Quintana-Escobar; Enrique Ibarra-Laclette; Víctor M. Loyola-Vargas (Plants)
In Coffea canephora, a direct somatic embryogenesis (SE) protocol has been established by pretreating plants with NAA and kinetin, followed by the induction of leaf explants in a liquid medium with BA. Through a transcriptomic analysis of 10 key moments of the induction of SE in C. canephora, we were able to establish that the transcriptional responses of this process are divided into four stages. These stages correspond to the pretreatment, characterized by the positive regulation of genes associated with cell wall remodeling, flavonoid biosynthesis, and antioxidant activity that prepare the explants for the intense cellular activity that represents the induction of SE. During the first few hours, the early response to induction occurs, characterized by the highest number of differentially expressed genes, most related to the response to multiple stimuli. At 24 h, a late response begins with the upregulation of genes related to energy production and the biosynthesis of amino acids. Finally, WOX, BBM, and ABI3 genes are upregulated during the embryogenic response. The downregulation of genes related to the circadian cycle, photomorphogenesis, photosynthesis, and chloroplast components were observed throughout the process. The detailed analysis of the primary transcriptional responses that occur during the SE of C. canephora helps us to clarify how auxins and cytokinins orchestrate the integration of different networks of plant metabolism and lead to the development of somatic embryos.